(untitled) (INTERNATIONAL JOURNAL OF SCIENCE AND TECHNOLOGY, 2025)
This article examines discursive and compensatory means in political discourse, focusing on their functions, classifications, and communicative impact. The study explores how various linguistic and rhetorical strategies shape political messages, influence public perception, and contribute to the construction of ideological narratives. By analyzing contemporary political texts, the research identifies key mechanisms used to manage political communication effectively. The findings highlight the role of discursive and compensatory techniques in shaping political debates, enhancing persuasion, and mitigating communicative failures.